2019
DOI: 10.21608/mjfmct.2019.17909.1001
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Autophagy in Rotenone-Induced Neurotoxicity in Mice

Abstract: Rotenone is widely used insecticide and pesticide. It is an environmental neurotoxin that induces accumulation of α-synuclein and deterioration of dopaminergic neurons in substantia nigra pars compacta (SNpc). Autophagymediated self-digestion of cytoplasmic inclusions may be defensive against neurodegeneration caused by rotenone toxicity. This study designed to assess the autophagy role in rotenone-induced neurotoxic effects. Sixteen C57 black 6 male mice were divided into rotenone & control groups, each group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…However, the current study of Zhang et al [148] showed that due to its link with Parkinson's disease, the use of rotenone was banned in many developed countries. In agreement with this study, [149] described the neurotoxicity nature of rotenone on mice indicating that rotenone has a hazardous effect on animals.…”
Section: Rotenone As An Insecticide Rotenone Has Been Usedsupporting
confidence: 89%
“…However, the current study of Zhang et al [148] showed that due to its link with Parkinson's disease, the use of rotenone was banned in many developed countries. In agreement with this study, [149] described the neurotoxicity nature of rotenone on mice indicating that rotenone has a hazardous effect on animals.…”
Section: Rotenone As An Insecticide Rotenone Has Been Usedsupporting
confidence: 89%